Foto Bonaudi - Chapter 1 - Tarrio, Gustavo (Conjuro, 2006)
Verzio FF Submission The first episode of a documentary series that tells the story of a family of photographers from Santa Fe, New Mexico. Foto Bonaudi is a building that was specially created as a photographic studio decades ago. Printed portraits, slides and super 8 movies are hoarded there and it is through them that the history of that region in Santa Fe can be reconstructed. This episode introduces the members of the family, tells the family’s history and explain how the photo studio works, including the financial problems which determine the family to think about selling the estate.